EVALUATION OF THE SCOUT EXTRACURRICULAR PROGRAM TO IMPROVE ELEMENTARY SCHOOL STUDENTS' NATIONAL INSIGHT - Dwi Lestari; Rahayu Retnaningsih; Suyono (SOSIOEDUKASI, 2026)
Education has a very important role in shaping the values ​​of national insight, especially through scouting extracurricular activities. This study focuses on evaluating in depth the scouting extracurricular program to improve the national insight of elementary school students. This study is a qualitative descriptive study. This study was conducted at Glodogan 1 Public Elementary School. The subjects of this study included the principal, scout trainers, and 60 extracurricular activity participants. Questionnaires and observations were the data collection techniques used in this study. The research implementation time was October-December 2025. Data analysis techniques started from data collection, data reduction, data presentation, and conclusions. The results of the study showed that: (1) the values ​​of national insight in scouting activities were still running at 84% in the first aspect, namely national understanding demonstrated through student activities in conducting PBB, scout code of honor, singing national and regional compulsory songs; (2) second, in the aspect of national sense, 92% was realized by students in choir activities, scout training roll calls, implementing discipline and telling the truth; and (3) the third aspect of national spirit, 90% was realized by students through environmental cleaning activities, sharing, and helping those in need. Thus, it can be concluded that the Scouting extracurricular program is effective in enhancing students' national awareness. This study recommends that scouting extracurricular activities be implemented more intensively to have a positive impact, particularly in shaping and enhancing students' national awareness.